Re-reuse of regenerated brownfields: Lessons from an Eastern European post-industrial city. (1st July 2018) - Martinat, Stanislav; Navratil, Josef; Hollander, Justin B.; Trojan, Jakub; Klapka, Pavel; Klusacek, Petr; Kalok, David
Abstract: Brownfields constitute a substantial portion of the land area in post-industrial cities. Many brownfields have been regenerated for various uses, addressing a range of extant problems in urban areas. However, re-use plans for current brownfields are driven by market demand and public sector prioritization and do not always meet the requirements of local residents and visitors. In this paper, we investigate how a range of brownfields re-use options are perceived by residents and visitors to the Landek area in the city of Ostrava (Czech Republic). By analysing the results of the questionnaire survey (n = 180) we found that future brownfields uses such as culture/sport and children's park are the most popular options. We found that gender was a statistically significant predictor of preferred reuse options. Women are strong supporters of the above-mentioned re-use options, while men tend to favour re-use options which promote industry. Remarkably, respondents, in general, lacked concrete ideas concerning alternative re-use options of brownfields, suggesting that professional urban planners can be of assistance in the planning of the future use of brownfield sites. Highlights: Perception of re-use options for particular brownfield is surveyed. Culture/sport and children's park are the most popular re-use options. Gender perspective significantly mirrors in the selection of favourite re-use options. Lack of ideas concerning alternative re-use options is obvious.